An approximate solution of the Yang - Mills equation on a spatially flat FRW cosmological background - Shchigolev, Victor (International Journal of Physical Research, 2019)
In this paper, an approximate solution for the Yang - Mills equation in a spatially flat Friedmann-Robertson-Walker universe is obtained. For this purpose, the well known method of solution of non-linear differential equations is used, viz. the homotopy perturbations method. This method has been developed as effective technique for solving different non-linear problems. Here, this method allowed us to obtain approximate solution for the essentially non-linear equation for the SO3 Yang-Mills fields on the curved space-time background of the spatially flat Friedmann-Robertson-Walker universe.